Potentiometric Studies on Some Binary and Mixed Ligand Complexes of UO2 (VI) [Part-III] - Lovina Dhir, (Mrs.); Diwan, B.D.; Mundhara, G.L. (Asian Journal of Chemistry, 2010)
Stability constants of binary complexes of UO2(VI) with nitrilotriacetic acid (NTA), lactic acid (LA) and protocatechuic acid (PCA) as ligands and of mixed ligand complexes of UO2(VI) with NTA as a primary ligand and LA and PCA as secondary ligands at 20, 35, 50° and in different ratios of water to non-aqueous solvents and at different ionic strengths have been determined. The effect of dielectric constant and ionic strength on the values of stability constants have been discussed on the basis of sterie factors and structural characteristics of complex formed.